The Development of a Mathematical Model of an Algorithm for Constructing an Individual Educational Trajectory for the Development of Methodological Competence among IT Discipline Teachers - Sapar Toxanov; Dilara Abzhanova; Aidos Mukhatayev; Andrii Biloshchytskyi; Svitlana Biloshchytska (MDPI AG, 2024)
This article explores contemporary models of the development of methodological competence, focusing on the needs of IT discipline teachers. The challenges in implementing these features within modern educational conditions are identified, underscoring the necessity for creating innovative teaching methods adapted to the requirements of IT teachers. By analyzing current trends in the educational environment, the authors highlight key stages in the continuous education system for teachers, including the mastering of basic education, adapting young teachers, and fostering their professional development. The article reveals the actual possibilities of developing the methodological competence of teachers as an ongoing endeavor to elevate their professional pedagogical culture. In the article, the authors propose a conceptual model within the domain of education, serving as the basis for constructing an efficient mathematical model which is specifically designed to create individualized learning trajectories for IT discipline teachers with the focus on managing the process of methodological competence development during the synthesis of training courses. The authors propose an innovative approach to teacher retraining, centered around individualized needs and abilities, with the aim of enhancing the quality of education in the field of information technology.